The Influence of Service Quality and Current Account Customer Trust on the Decision to Save Funds at PT. Bank Central Asia Tbk Bekasi Main Branch Office - Ali Mutaufiq; Sawqi Saad El Hasan; Ermi Herawati; Destiana Utarinda; Ana Wijandari (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
The decision to save funds is often influenced by a variety of factors, including an individual's financial goals, income, expenses, and overall financial health. Service quality and customer trust in a bank's current account may also play a role in an individual's decision to save funds The research method used in this study uses quantitative methods or often called traditional methods, because this method has been used for a long time so that it has become a tradition for research. The result is Quality of Service on Decision to Save Funds, knowing that the results of tcount > ttable are (5.876 > 1.974) and a significance of 0.000 <0.05, then Service Quality has a positive and significant effect on Decisions to Save Funds, so H1 is Accepted. Current Account Customer Confidence in the Decision to Save Funds, knowing that the results of tcount > ttable are (6.571> 1.974) and a significance of 0.000 <0.05, then the Current Account Customer Trust has a positive and significant effect on the Decision to Save Funds, so H2 is accepted. Quality of Service and Trust of Current Account Customers simultaneously (together) have a positive and significant effect on the Decision to Save Funds, by knowing the results of Fcount > Ftable (273.186 > 3.05) and a significance of 0.000 <0.05 and with a coefficient of determination or r square (R2) of 0.768 or 76.8% while the rest (100% - 76.8% = 23.2%) is influenced by other variables outside this regression equation or variables not examined. Then the Quality of Service and Trust of Demand Deposits together have a significant positive effect on the Decision to Save Funds, so that H3 is Accepted.